Late Cadomian rifting of the NW Gondwana margin and the reworking of Precambrian crust – evidence from bimodal magmatism in the early Paleozoic Moroccan Meseta. Issue 16 (2nd November 2021) - Ouabid, Muhammad; Garrido, Carlos J.; Ouali, Houssa; Harvey, Jason; Hidas, Károly; Marchesi, Claudio; Acosta-Vigil, Antonio; Dautria, Jean-Marie; El Messbahi, Hicham; Román-Alpiste, Manuel J.
ABSTRACT: The Meseta Goaïda magmatism, which occurs as gabbro, dolerite and rhyolitic intrusions in the Neoproterozoic basement and Cambrian platform sedimentary series of the Moroccan Hercynian orogen, has been ascribed to the Variscan orogenesis in the late Palaeozoic. Here, we provide new LA–ICP-MS U-Pb zircon ages – ranging from c. 519 Ma to c. 479 Ma – of this magmatism that reveal, for the first time in the Moroccan Central Meseta, the existence of early Cambrian to early Ordovician bimodal magmatism. Inherited zircons in these magmatic rocks yield dates that range from c. 1.2 to 1.0 Ga and c. 0.63 to 0.50 Ga. This inheritance suggests provenance from Precambrian crustal sources in the Cadomian‒Pan-African of the NW margin of the West African Craton, which is buried beneath the currently exposed Paleozoic Moroccan Meseta. The affinity of this early Palaeozoic magmatism is mainly tholeiite to transitional for the mafic rocks and high-K calc-alkaline for the silicic rocks. The Cambrian–Ordovician age and varying parental magma signature – as shown by trace element and Sr-Nd-Pb isotopic data from this magmatism and its Neoproterozoic granitoid basement rocks – indicate that the Moroccan Meseta early-Paleozoic magmatism might be associated with the weakening of the continental lithosphere during the early stages of rifting during the Cambrian–Ordovician along the NW Gondwana margin. This is supported by the presence of inherited zircons derived from reworking of the Precambrian crust in the early-Palaeozoic magmas.